Cost-Effectiveness Analysis of a Prescription Digital Therapeutic for the Treatment of Opioid Use Disorder - Fulton F. Velez; Daniel C. Malone (Journal of Market Access & Health Policy)
The lack of adequate treatment for many patients with opioid use disorder (OUD) has led to high medical costs ($90B in 2020). An analysis of the cost-effectiveness (cost-utility) of reSET-O, the first and only FDA-approved prescription digital therapeutic (PDT) for the treatment of OUD, is needed to inform value assessments and healthcare decision making. To evaluate the cost-utility of reSET-O in conjunction with treatment-as usual (TAU) compared to TAU alone. A third-party payer-perspective decision analytic model evaluated the cost-effectiveness of reSET-O + TAU relative to TAU (i.e., oral buprenorphine, face-to-face counseling, and contingency management [immediate rewards for negative drug tests logged]) alone over 12 weeks. Clinical effectiveness data (retention in therapy and health state utilities) were obtained from the peer-reviewed literature, while resource utilization and cost data were obtained from a published claims data analyses. Over 12 weeks, the addition of reSET-O to TAU resulted in a gain of 0.003 quality-adjusted life years (QALYs), and $1,014 lower costs, resulting in economic dominance vs. TAU. reSET-O + TAU’s was economically dominant (less costly, more effective) vs. TAU alone over 12 weeks, a result that was driven by a reduction in medical costs after initiation of reSET-O observed in a recent real-world claims analysis.